[Rezension von: Ptacek, James, 1953-, Feeling trapped] - DeKeseredy, Walter S. (The British journal of criminology, 2024)
Featured in a recent issue of Critical Criminology, the results of an exploratory bibliometric study conducted by me, Ping Lam Ip, and Andrea DeKeseredy empiric